Effort–reward imbalance is associated with the metabolic syndrome — Findings from the Mannheim Industrial Cohort Study (MICS). (15th January 2015) - Schmidt, Burkhard; Bosch, Jos A.; Jarczok, Marc N.; Herr, Raphael M.; Loerbroks, Adrian; van Vianen, Annelies E.M.; Fischer, Joachim E.
Abstract: Background/objectives: Job stress is a predictor of cardiovascular disease incidence and mortality and the metabolic syndrome (MetS) represents one of the key pathways potentially underlying those associations. Effort–reward imbalance (ERI) represents one of the most influential theoretical work stress models, but evidence on its relationship with MetS remains sparse and with only limited generalizability. We therefore aimed to determine this association in a large occupational sample with different occupational groups. Methods: The present study used cross-sectional data from an industrial sample in Germany (n = 4141). ERI was assessed by a validated 10-item questionnaire. MetS was defined according to a joined interim statement of six expert associations involved with MetS, stating that three out of five risk factors (raised blood pressure, elevated triglycerides, low high density lipoprotein, raised fasting glucose and central obesity) qualify a patient for MetS. Multivariable associations of ERI, and its subcomponents "effort" and "reward", with MetS were estimated by logistic regression-based multivariate odds ratios (ORs) with 95% confidence intervals (CIs). Results: ERI (continuous z-score) was positively associated with MetS (zERI: OR = 1.14, 95% CI = 1.03–1.26). The association was more prominent in males (zERI: OR 1.20, 95% CI = 1.07–1.33) and in younger employees (age 18–49 zERI: OR = 1.24, 95% CI = 1.09–1.40). Analysis of the ERI subcomponents yielded weak associations of both effort (zEffort: OR = 1.12, 95% CI = 1.00–1.25) and reward (zReward: OR = 0.92, 95% CI = 0.84–1.00) with MetS. Conclusions: ERI is associated with increased occurrence of MetS, in particular among younger men. Further longitudinal studies are needed to determine the temporal relation of these associations.